Adipose-derived mesenchymal stem cells (AdMSC) for the treatment of secondary progressive multiple sclerosis: A triple blinded, placebo controlled, randomized phase I/II safety and feasibility study. - Fernández Fernández, Óscar; Izquierdo, Guillermo; Fernández Sánchez, Victoria Eugenia; Leyva-Fernández, Laura; Reyes, Virginia; Guerrero, Miguel; León, Antonio; Arnáiz, Carlos; Navarro, Guillermo; Páramo, Mª Dolores; De la Cuesta, Antonio; Soria, Bernat; et al. (Public Library of Science, 2018)
Background Currently available treatments for secondary progressive multiple sclerosis(SPMS) have limited efficacy and/or safety concerns. Adipose-mesenchymal derived stem cells(AdMSCs) represent a promising option and can be readily obtained using minimally invasive procedures. Patients and methods In this triple-blind, placebo-controlled study, cell samples were obtained from consenting patients by lipectomy and subsequently expanded. Patients were randomized to a single infusion of placebo, low-dose(1x10^6 cells/kg) or high-dose(4x10^6 cells/kg) autologous AdMSC product and followed for 12 months. Safety was monitored recording adverse events, laboratory parameters, vital signs and spirometry. Expanded disability status score (EDSS), magnetic-resonance-imaging, and other measures of possible treatment effects were also recorded. Results Thirty-four patients underwent lipectomy for AdMSCs collection, were randomized and thirty were infused (11 placebo, 10 low-dose and 9 high-dose); 4 randomized patients were not infused because of karyotype abnormalities in the cell product. Only one serious adverse event was observed in the treatment arms (urinary infection, considered not related to study treatment). No other safety parameters showed changes. Measures of treatment effect showed an inconclusive trend of efficacy. Conclusion Infusion of autologous AdMSCs is safe and feasible in patients with SPMS. Larger studies and probably treatment at earlier phases would be needed to investigate the potential therapeutic benefit of this technique.
Keywords: Esclerosis múltiple - Tratamiento; Ensayos clínicos; Células madre; Tejido adiposo; Esclerosis múltiple secundariamente progresiva; Refractaria a tratamientos convencionales; Células madre mesenquimales derivadas de tejido adiposo; Ensayo clínico fase I/II